2007
DOI: 10.3390/medicina43050045
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of late left ventricular systolic dysfunction in patients with acute coronary syndrome during the acute period

Abstract: Summary. The aim of the study was to create the model of the combination of clinical and echocardiographic determinants during the acute period of acute coronary syndromes for the prognostication of the risk for left ventricular dysfunction after one year.We Medicina (Kaunas) 2007; 43(5) -http://medicina.kmu.lt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…This study as a part of project "eHealth for Regions" was partly financed by EU Interreg IIIb program in 2004-2006. 1 Širdies, krūtinės ir kraujagyslių chirurgijos klinika, 2 Kardiologijos institutas, 3 Profilaktinės medicinos katedra Raktažodžiai: telemedicina, telekardiologija, telekonsultacijos.…”
Section: Acknowledgementunclassified
See 1 more Smart Citation
“…This study as a part of project "eHealth for Regions" was partly financed by EU Interreg IIIb program in 2004-2006. 1 Širdies, krūtinės ir kraujagyslių chirurgijos klinika, 2 Kardiologijos institutas, 3 Profilaktinės medicinos katedra Raktažodžiai: telemedicina, telekardiologija, telekonsultacijos.…”
Section: Acknowledgementunclassified
“…Ischemic heart disease (IHD) in European countries over decades has been a common cause of sudden death (up to 55% of all cases) and also has a high rate of mortality, morbidity, and hospital admission and requires long and intensive hospital care (1,2). The first idea of transtelephonic transmissions of electrocardiograms (ECGs), ballistocardiograms (BCGs), and electroencephalograms (EEGs) in the former Soviet Union was developed by Prof. Zigmas Januškevičius and implemented in 1962, when transmissions from Kaunas to Moscow were performed (3).…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies have shown that a history of heart failure (EF <40%) also contributes to a poor prognosis of patients with chronic coronary syndromes, because the most common cause of heart failure is myocardial infarction (5,6). The GRACE registry suggests that acute heart failure 3 to 4 times increased risk of death after MI during 6-month period (7), and by data of other studies, the risk of death was even greater after MI and unstable angina, complicated with heart failure, during an 18-month period (8,9). Our data show that Killip class III or IV is one of the major risk factor for one-year mortality.…”
Section: Discussionmentioning
confidence: 99%